Analysis of Cross-Border Trade Between Countries: Normative Study Between Indonesia and Countries with Direct Land Borders - E. Imma Indra Dewi Windajani; Etty Indrawati; Koleta Donna Indhayana Putri (West Science Law and Human Rights, 2024)
Based on Government Regulation Number 34 Year of 2019 on Border Trade, economic transactions in cross-border trade are permitted with certain restrictions. These limitations include the type of goods, the quantity of purchases, and the trading system of trade goods. The types and maximum purchase limits are regulated in the bilateral Border Trade Agreement (BTA) and Border Crossing Agreement (BCA). In practice, transactions exceed the limits of transaction value specified in bilateral agreements and governing laws and regulations, causing losses to the state. There are two purposes of this research. The first is to explore and analyze the factors causing irregularities in cross-border trade transactions and the second is to explore the efforts to minimize them. This research is normative legal research through library research by tracing secondary data in the form of primary legal materials and secondary legal materials, using documentation methods and instruments in the form of document studies. Then, data were analyzed using qualitative analysis. There are two results of this research. The first is four factors that cause deviations in cross-border trade transactions, including economic factors, infrastructure factors, and juridical factors. The second is the efforts that can be made to minimize deviations in cross-border trade transactions including preemptive efforts in the form of instilling good values that are internalized into a person, preventive efforts in the form of preventive actions, and repressive efforts in the form of law enforcement actions.